Using the Evaluation of Social Interaction in a community-based program for persons with traumatic brain injury. - Simmons CD; Griswold LA (Scandinavian Journal of Occupational Therapy, 2010)
The purpose of this study was to examine the utility of the Evaluation of Social Interaction (ESI) in a community-based program for persons with traumatic brain injury (TBI), as well as its effectiveness in measuring occupational therapy intervention. Ten people who experienced a TBI and were participating in a community-based program were a convenience sample for this study. The Occupational Therapy Intervention Process Model (OTIPM) provided the theoretical framework. The ESI provided a pre-test performance measure and also served as a guide for an eight-week occupational therapy intervention program, and as a post-test to measure intervention effectiveness. This study showed that the ESI was effective in guiding therapist intervention related to social skill performance of participants during their participation in a community-based program. As a group, the difference between pre and post ESI logit measures was also significant ( t=4.977, p=0.001). The study provides initial considerations for the utility of the ESI to guide intervention related to social skill performance during daily occupations. It further documents the effectiveness of the ESI in measuring occupational therapy intervention, based on OTIPM, and supports occupational therapy services provided in a community-based program context for those living with TBI.